Overcoming the translational crisis of contemporary psychiatry: converging phenomenological and spatiotemporal psychopathology - Northoff, Georg; Daub, Jonas; Hirjak, Dusan (Molecular psychiatry, 2023)
Despite all neurobiological/neurocomputational progress in psychiatric research, recent authors speak about a ‘crisis of contemporary psychiatry’. Some argue that we do not yet know the computational mechanisms underlying the psychopathological symptoms (‘crisis of mechanism’) while others diagnose a neglect of subjectivity, namely first-person experience (‘crisis of subjectivity’). In this perspective, we propose that Phenomenological Psychopathology, due to its focus on first-person experience of space and time, is in an ideal position to address the crisis of subjectivity and, if extended to the brain’s spatiotemporal topographic-dynamic structure as key focus of Spatiotemporal Psychopathology, the crisis of mechanism. We demonstrate how the first-person experiences of space and time differ between schizophrenia, mood disorders and anxiety disorders allowing for their differential-diagnosis - this addresses the crisis of subjectivity. Presupposing space and time as shared features of brain, experience, and symptoms as their “common currency”, the structure of abnormal space and time experience may also serve as template for the structure of the brain’s spatiotemporal neuro-computational mechanisms - this may address the crisis of mechanism. Preliminary scientific evidence in our examples of schizophrenia, bipolar disorder, anxiety disorder, and depression support such clinically relevant spatiotemporal determination of both first-person experience (crisis of subjectivity) and the brain’s neuro-computational structure (crisis of mechanism). In conclusion, converging Phenomenological Psychopathology with Spatiotemporal Psychopathology might help to overcome the translational crisis in psychiatry by delineating more fine-grained neuro computational and -phenomenal mechanisms; this offers novel candidate biomarkers for diagnosis and therapy including both pharmacological and non-pharmacological treatment.